Effect of early and current Helicobacter pylori infection on the risk of anaemia in 6.5-year-old Ethiopian children - Taye, Bineyam (BMC Infect Dis, 2015)
BACKGROUND: Epidemiological and clinical studies in high income countries have suggested that Helicobacter pylori (H. pylori) may cause anaemia, but evidence is lacking from low income countries.We examined associations between H. pylori infection in early childhood and anaemia at the age of 6.5 years in an Ethiopian birth cohort. METHODS: In 2011/12, 856 children (85.1 % of the 1006 original singletons in a population-based birth cohort) were followed up at age six and half. An interviewer-led questionnaire administered to mothers provided information on demographic and lifestyle variables. Haemoglobin level and red cell indices were examined using an automated haematological analyzer (Cell Dyn 1800, Abbott, USA), and stool samples analyzed for H. pylori antigen. The independent effects of H. pylori infection (measured at age 3.5 and 6.5 years) on anaemia, haemoglobin level, and red cell indices (measured at age 6.5 years) were determined using multiple logistic and linear regression. RESULTS: The prevalence of anemia was 34.8 % (257/739), and the mean (SD) haemoglobin concentration was 11.8 (1.1) gm/dl. Current H. pylori infection at age 6.5 years was positively, though not significantly related to prevalence of anaemia (adjusted OR, 95 % CI, 1.15; 0.69, 1.93, p = 0.59). Any H. pylori infection up to age 6.5 years was significantly associated with an increased risk of anaemia at age 6.5 (adjusted OR, 95 % CI, 1.68; 1.22, 2.32, p = 0.01). A significant reduction in haemoglobin concentration and red cell indices was also observed among children who had any H. pylori infection up to age 6.5 (Hb adjusted β = −0.19, 95 % CI, −0.35 to −0.03, p = 0.01; MCV adjusted β = −2.22, 95 % CI, −3.43 to −1.01, p = 0.01; MCH adjusted β = −0.63, 95 % CI, −1.15 to - 0.12, p = 0.01; and MCHC adjusted β = −0.67, 95 % CI, −1.21 to −0.14, p = 0.01), respectively. CONCLUSION: This study provides further evidence from a low income country that any H. pylori infection up to age 6.5 is associated with higher prevalence of anaemia, and reduction of haemoglobin level and red cell indices at age 6.5. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-015-1012-y) contains supplementary material, which is available to authorized users.